A cross sectional study on knowledge, attitude and practice of dengue fever among high school students in Villupuram municipality of Villupuram - Singaravel, Sasikaladevi S.; Kandaswamy, Elayaraja K. (International Journal Of Community Medicine And Public Health, 2018)
Background: School-based education is an important way of transfer of knowledge and practices of dengue from classrooms to homes which helps to maintain clean environment for source reduction of dengue. Thus, this study was conducted with the main purpose of examining the knowledge, attitude and practices of dengue fever among school children in Villupuram. Methods: The study area was at high school students of Villupuram municipality from November 2017 to December 2017. The sample size is calculated from Dimbulagedara et al study where the prevalence was 47.2%. Considering Confidence level of 95%, relative precision of 7% the sample size derived was 216. Multistage sampling was used. The required information obtained by means of validated questionnaire. Results: Majority were of 14 years. More than 75% had a good knowledge on breeding source of infection, 50% were not aware that trashes were a breeding source with a significant p value of <0.05 between age and knowledge. The major source of knowledge was the school. More than half of them were of attitudes that they are not at risk of dengue. 59.7% of the respondents felt they were scared if they were to be infected. Removal of water stagnation (80.1%) was the commonly practiced preventive measures. Conclusions: School students had adequate basic knowledge regarding dengue. There were some misconceptions regarding to dengue. Personal protection and trash removal was least practiced which can be made successful by behaviour change, communication.